Proposta de zoneamento geoambiental da bacia hidrográfica do Ribeirão do Ouro no município de Pirassununga (SP) - Lossardo, Luiz Fernando (Universidade Federal de São Carlos, 2014)
This study aimed to gather information about the physical environment in the Basin Ribeirão do Ouro in Pirassununga, SP to, and a better understanding of the place, the subsidy for the discussion of environmental management and more sustainable development of the territory covered by this area of study through its zoning geoenvironmental. The Basin Ribeirão do Ouro is located almost entirely in the city of Pirassununga, São Paulo, totaling an area of 12,594.81 hectares or 125.94 square kilometers in length and are fully contained in the basin of Rio Mogi. Because it is a region bordering the western plateau and Paulista Paulista Peripheral Depression, both unit morphostructural the Paraná Sedimentary Basin, the relief of the study area varies between undulated and wavy respectively. After all survey process, using existing laboratory tests, field work for checking of information, analysis through the use of technologies of remote sensing and GIS, cartographic materials were generated new very important, among them, the Charter Zoning Geoenvironmental. The zoning proposal resulting from this work showed 17 geoenvironmental distinct areas, which seek to demonstrate its main features, weaknesses and future scenarios for the use and occupation of these areas more sustainable.
Keywords: Zoneamento ambiental; Planejamento regional; Gerenciamento de bacias hidrográficas; Pirassununga (SP); ENGENHARIAS